2023
DOI: 10.1002/apxr.202300032
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Phase Growth, Stabilization, and Electrical Properties of B Phase VO2 Films Grown on Mica by Reactive Magnetron Sputtering

Abstract: The VO2 metastable (B) phase is of interest for applications in temperature sensing, bolometry, and Li‐ion batteries. However, single‐phase growth of thin films of this metastable phase is a challenge because vanadium oxide exhibits many polymorphs and the VO2 stable (M1) phase is usually present as a secondary phase. Additionally, the phase transition at 350 °C in the (B) phase severely narrows the processing window for achieving phase‐pure films. Here, single‐phase growth of 5‐to 50‐nm thick VO2 (B) films on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In view of the strong chemical interaction between VO 2 and the substrate, which causes significant strain during MIT, they proposed van der Waals epitaxy as a tool to effectively alter the phase transition kinetics in VO 2 -like systems. Ekström et al further demonstrated van der Waals epitaxy of stress-free thin films of VO 2 nonlayered materials by using magnetron sputtering to grow VO 2 films on mica substrates. , Zhang et al used the differential scanning calorimetry (DSC) technique to study the transformation kinetics of tungsten-doped VO 2 nanoparticles . They combined the isoconversional kinetics with the classical nucleation kinetics model to reasonably explain the asymmetry of MIT in the heating and cooling stages caused by tungsten doping.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the strong chemical interaction between VO 2 and the substrate, which causes significant strain during MIT, they proposed van der Waals epitaxy as a tool to effectively alter the phase transition kinetics in VO 2 -like systems. Ekström et al further demonstrated van der Waals epitaxy of stress-free thin films of VO 2 nonlayered materials by using magnetron sputtering to grow VO 2 films on mica substrates. , Zhang et al used the differential scanning calorimetry (DSC) technique to study the transformation kinetics of tungsten-doped VO 2 nanoparticles . They combined the isoconversional kinetics with the classical nucleation kinetics model to reasonably explain the asymmetry of MIT in the heating and cooling stages caused by tungsten doping.…”
Section: Introductionmentioning
confidence: 99%